We should move away from a focus on individual resilience towards building resilient systems. (9th November 2021) - Johal, Harleen Kaur; Prout, Rachel; Birchley, Giles; Huxtable, Richard
Abstract : Too much emphasis has been placed on the resilience of individuals and too little on the resilience of the health system, argue Harleen Kaur Johal and colleagues